Business Sustainability Assessment Tools—Their Impact on Corporate Sustainability and Reputation: The Case of Listed Companies in Vietnam - Nguyen Phu Giang; Dao Ngoc Ha; Tran Nguyen Bich Hien (SAGE Open, 2025)
To assess the impact of sustainability assessment tools on the sustainability of the business and measure the impact of these tools and the business’s sustainability on the business’s reputation and brand. Scoring the sustainability level according to each criterion of each sustainability assessment tool, run AMOS software to measure the impact of each assessment tool on the sustainability and reputation of the business. This article aims to present and discuss the art of sustainability assessment using integrated assessment tools, including life cycle assessment, data-based assessment of sustainability reports, impact assessment with stakeholders and from stakeholders to make recommendations for further development, consistent with ontology, epistemology, and methodology of aspects of sustainability science. By using integrated tools to assess a business’s sustainability, it is possible to ensure that its activities match the needs and expectations of its stakeholders. This can help build trust and goodwill with the community and contribute to the long-term and sustainable success of the business.